Cumulus expansion, nuclear maturation and connexin 43, cyclooxygenase-2 and FSH receptor mRNA expression in equine cumulus-oocyte complexes cultured in vitro in the presence of FSH and precursors for hyaluronic acid synthesis - Aiudi Giulio; Gérard Nadine; Martoriati Alain; Maritato Filippo; Caillaud Maud; Dell'Aquila Maria; Minoia Paolo; Goudet Ghylène (BMC, 2004)
Abstract The aim of this study was to investigate cumulus expansion, nuclear maturation and expression of connexin 43, cyclooxygenase-2 and FSH receptor transcripts in equine cumuli oophori during in vivo and in vitro maturation in the presence of equine FSH (eFSH) and precursors for hyaluronic acid synthesis. Equine cumulus-oocyte complexes (COC) were cultured in a control defined medium supplemented with eFSH (0 to 5 micrograms/ml), Fetal Calf Serum (FCS), precursors for hyaluronic acid synthesis or glutamine according to the experiments. After in vitro maturation, the cumulus expansion rate was increased with 1 microgram/ml eFSH, and was the highest with 20% FCS. It was not influenced by precursors for hyaluronic acid synthesis or glutamine. The expression of transcripts related to cumulus expansion was analyzed in equine cumulus cells before maturation, and after in vivo and in vitro maturation, by using reverse transcription-polymerase chain reaction (RT-PCR) with specific primers. Connexin 43, cyclooxygenase-2 (COX-2) and FSH receptor (FSHr) mRNA were detected in equine cumulus cells before and after maturation. Their level did not vary during in vivo or in vitro maturation and was influenced neither by FSH nor by precursors for hyaluronic acid synthesis. Results indicate that previously reported regulation of connexin 43 and COX-2 proteins during equine COC maturation may involve post-transcriptional mechanisms.